Differential quadrature in ordinary differential equations - Latifa, FAID (Faculty of Mathematics and computersciences Department of Mathematics - Option : Mathematics and numerical analysis, 2020)
In this memory investigate the Differential Quadrature Method, to approximate the solution of Differential Ordinary Equations. Numerical examples are presented in Hammerstein integral equations.
Keywords: Differential Quadrature Method, ODE, error of approximation, Norms, Banach space.